AKIBAT HUKUM PENERBITAN COVERNOTE OLEH NOTARIS/ PPAT TERHADAP PIHAK-PIHAK DALAM PERJANJIAN KREDIT PERBANKAN - MICHAEL BOY SEMBIRING (PREMISE LAW JURNAL, 2018)
In practice, a covernote is made by a reliable Notary/PPAT in disbursingfunds in a credit contract. Covernote is not regulated in the Notarial Act ad in theGovernment Regulation on PPAT, or in the Law on Banking. The researchproblems are how about the authority of a Notary/PPAT to issue covernote for theinterest of stakeholders in a credit contract, how about the legal certainty ofcovernote issued by a Notary/PPAT to disburse credit in banking credittransaction, and how about the liability for a Notary and debtor when theNotary/PPAT cannot settle the case of the Hypothecation on time specified in thecovernote.The research used juridical normative and descriptive analytic method.Primary data were gathered by conducting interviews, secondary data wereobtained from Law No. 30/2004 on Notarial Position, Law No. 4/1996 onHypothecation, PP No. 37/1998 on the Regulation on the Position of the OfficialEmpowered to Draw Up Land Deeds, law No. 7/1992 on Banking, and Law No.10/1998 on the Amendment of Law No. 7/1992 on Banking. Secondary data wereobtained from books and tertiary data from dictionaries and dictionaries of law.Keywords: Covernote, Credit, Banking